2017
DOI: 10.1093/ije/dyx141
|View full text |Cite
|
Sign up to set email alerts
|

The duration of protection of school-aged BCG vaccination in England: a population-based case–control study

Abstract: School-aged BCG vaccination offered moderate protection against tuberculosis for at least 20 years, which is longer than previously thought. This has implications for assessing the cost-effectiveness of BCG vaccination and when evaluating new TB vaccines.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
34
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(39 citation statements)
references
References 20 publications
4
34
0
1
Order By: Relevance
“…This latter finding could have implications for understanding different levels of protection from BCG across populations with varying intensity of Mtb transmission, protection being weakest in high-TB-burden settings (121). In addition, the study by Verrall et al found evidence of BCG protection against infection up until the age of 30 years, which is consistent with recent studies suggesting that BCG protection against TB disease lasts at least 20 years when given at birth or at school age (122,123).…”
Section: Insights Gained From Bcg Vaccination In Human Studiessupporting
confidence: 65%
“…This latter finding could have implications for understanding different levels of protection from BCG across populations with varying intensity of Mtb transmission, protection being weakest in high-TB-burden settings (121). In addition, the study by Verrall et al found evidence of BCG protection against infection up until the age of 30 years, which is consistent with recent studies suggesting that BCG protection against TB disease lasts at least 20 years when given at birth or at school age (122,123).…”
Section: Insights Gained From Bcg Vaccination In Human Studiessupporting
confidence: 65%
“…Supporting evidence for this hypothesis is found in the literature [36] indicating that the protective effects of the BCG against TB, can last from 15 to 60 years after vaccination, with longer lasting effects when the vaccine is administered during the rst year of life. [32] A recent study indicated that "school-aged BCG vaccination offered moderate protection against tuberculosis for at least 20 years, which is much longer than previously thought" [32].…”
Section: Discussionmentioning
confidence: 66%
“…The impact of infant BCG vaccination on pulmonary disease in adolescence and adults, which is responsible for driving the cycle of Mtb transmission in high TB incidence countries, is reduced by the fact that efficacy of infant BCG vaccination is not durable into adulthood (Sterne et al, 1998). Systematic reviews illustrate that, except for a handful of studies in low TB burden settings (Aronson et al, 2004;Barreto et al, 2005;Mangtani et al, 2018), BCG-induced protection wanes to zero by 10-15 years after vaccination (Abubakar et al, 2013;Sterne et al, 1998).…”
Section: Pre-exposure Approaches To Infant Vaccinationmentioning
confidence: 99%